3.4k views
2 votes
What is 1-4-x-(4-1)=-x-2-(4) With your work shown

User James Dunn
by
6.1k points

1 Answer

4 votes

Lets take this step by step.

1-4-x-(4-1)=-x-2-(4)

first, we'll simplify the parentheses on the left side of the equation.

1-4-x-3=-x-2-(4)

second, we'll combine like terms on the left side.

-6-x=-x-2-(4)

third, we'll combine like terms on the right side of the equation.

-6-x=-6-x

since these are equal, (x=x), we have infinitely many solutions.

User GhassanPL
by
6.1k points